2017
DOI: 10.1007/s00590-017-2001-1
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided cement sacroplasty (CSP) as pain therapy in non-dislocated insufficiency fractures

Abstract: IntroductionIn elderly patients with reduced bone quality, insufficiency fractures of the sacrum are relatively common and are typically associated with severe disabling pain. The objective of the present study was to examine the feasibility of cement augmentation by CSP, to determine post-interventional leakages and other complications, and to present the outcome of pain over the course of 18 months.Materials and methodsIn 23 patients (20 women and 3 men) with an average age of 81.3 (71–92) years, a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
9
0
9
Order By: Relevance
“…It has been repeatedly shown that sacroplasty rapidly reduces pain and improves mobility and activities of daily living [3, 15 -21]. It follows that this therapeutic option should be considered for patients suffering continuing crippling pain from non-dislo- Analogously to vertebroplasty, cement augmentation in sacroplasty can be performed without [15 -18, 31, 32] or after osteoplastic extension of the spongious space [33], by balloon kyphoplasty [11,19,26,34] or radiofrequency kyphoplasty [35,36]. The most commonly used approach has been administration of cement through an inserted hollow needle as in vertebroplasty [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been repeatedly shown that sacroplasty rapidly reduces pain and improves mobility and activities of daily living [3, 15 -21]. It follows that this therapeutic option should be considered for patients suffering continuing crippling pain from non-dislo- Analogously to vertebroplasty, cement augmentation in sacroplasty can be performed without [15 -18, 31, 32] or after osteoplastic extension of the spongious space [33], by balloon kyphoplasty [11,19,26,34] or radiofrequency kyphoplasty [35,36]. The most commonly used approach has been administration of cement through an inserted hollow needle as in vertebroplasty [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, there may be cement leakage and this is not always asymptomatic [32]. The osteoplastic procedure may also lead to leakages, either symptomatic or asymptomatic [33,34,36]. Leakages may be minimised if the complex anatomy of the sacral bone is born in mind, simple access pathways are selected depending on the fracture zone [26] -, if radiological visualisation during the operation is good [34], and if osteoplastic procedures are used if at all possible [33,35,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Eine Zusammenfassung der Zugangswege findet sich bei Andresen et al [30]. Aus unserer Sicht sind die Zugangswege über die kurze und transiliakale Achse technisch am besten durchführbar, es lassen sich hiermit alle Frakturzonen nach Denis et al [44] gut erreichen [64].…”
Section: Frakturtypenunclassified
“…Der eingebrachte PMMA-Zement bei der ZSP ist ca. doppelt so viskös wie bei der VSP [64] (▶Abb. 4 und ▶Abb.…”
Section: Frakturtypenunclassified
See 1 more Smart Citation